The Issue Decision of Manager‐Owners under Information Asymmetry - BRADFORD, WILLIAM D. (Journal of Finance, 1987)
ABSTRACT A firm must issue common stock in order to undertake a new investment, and the firm's manager‐owners can value the firm more accurately than the market. The ability of the manager‐owners to trade in the firm's shares during the issue (a) reduces the investments that are foregone because of the market's mispricing the firm's shares, (b) changes the size and direction of the stock price change when the firm announces a new stock issue, and (c) changes the market value of the firm before and after the issue announcement, whether or not it decides to issue.